A Comparative Analysis of Internal Radiation vs Box System in Treatment Efficacy and Patient Survival of Advanced Stage Cervical Cancer - Mona Galatia Marpaung; Teuku Mirza Iskandar; Noor Pramono; Suhartono Suhartono (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Objectives: To evaluate the comparative effectiveness of brachytherapy and the box system in therapeutic success and patient survival in cervical cancer, along with associated prognostic factors.Methods: This retrospective analytical study used medical records from the Obstetrics & Gynecology Oncology Clinic and Radiotherapy Unit at Dr. Kariadi General Hospital in Semarang. The study included cervical cancer patients with stage IIB-IIIB disease who were treated between January 2017 and December 2022. Data analysis involved both statistical methods and survival analysis using the Kaplan-Meier approach.Results: During the 2017-2022 study period, a total of 939 patients with stage IIB-IIIB cervical cancer who completed full radiation therapy were evaluated for their 2-year survival rate. The cohort included 89 patients in the box system group and 850 in the brachytherapy/internal radiation group. Complete response was achieved in 46.1% of box system patients compared to 75.5% in the brachytherapy group (p<0.0001); partial response rates were 53.9% and 24.5%, respectively. Kaplan-Meier analysis showed a 2-year survival rate (2 YSR) of 41.6% for the box system and 64.0% for brachytherapy. The mean survival time was 15.37 months for the box system and 19.09 months for brachytherapy.Conclusion: Internal radiation therapy (brachytherapy) showed significantly better clinical outcomes compared to the box system approach. It resulted in a longer mean survival time (19.09 vs 15.37 months; p<0.001) and higher 2-year survival rates (64.0% vs 41.6%; log-rank p<0.001).Keywords: Cervical cancer, box system, brachytherapy, therapy response, survivalPerbandingan antara Radiasi Interna vs Box System dalam KeberhasilanTerapi dan Kelangsungan Hidup Pasien Kanker Servik Stadium LanjutAbstrakTujuan: Penelitian ini bertujuan untuk mengetahui perbandingan radiasi interna dan box system dalam keberhasilan terapi dan kelangsungan hidup pasien kanker serviks serta faktor-faktor yang memengaruhi.Metode: Penelitian ini menggunakan metode analitik retrospektif dengan menggunakan rekam medis Poli Kandungan dan Onkologi dan Instalasi Radioterapi RSUP Dr. Kariadi Semarang. Subyek penelitian adalah pasien kanker servik stadium IIB-IIIB mulai periode januari 2017-Desember 2022. Analisis statistika menggunakan analisis analitik dan analisis survival menggunakan metode Kaplan Meier.Hasil: Hasil penelitian menunjukkan bahwa selama tahun 2017– 2022 didapatkan total 939 pasien dengan diagnosis kanker servik stadium IIB-IIIB yang menjalankan terapi radiasi lengkap dan dapat dilakukan evaluasi survival rate 2 tahun. Total subjek pada kelompok box system sebanyak 89, sedangkan kelompok brakiterapi/radiasi interna sebanyak 850 subjek. Respon terapi komplet sebesar 46,1% pada kelompok box system, dan 75,5% pada kelompok radiasi interna, respon terapi parsial 53,9% pada kelompok box system dan 24,5% pada kelompok radiasi interna, dengan nilai p <0.0001. Analisis survival dengan metode Kaplan -Meier didapatkan 2-YSR 41,6% pada kelompok Box system, sedangkan 64% pada kelompok radiasi interna sedangkan mean survival time pada kelompok box system 15,37 bulan dan kelompok radiasi interna 19,09 bulan dengan nilai p <0.001Kesimpulan: Pemberian radiasi interna memberikan keberhasilan terapi klinis yang lebih tinggi dengan nilai mean survival time lebih tinggi. Pemberian radiasi interna memberikan kelangsungan hidup 2 tahun sebanyak 64%, sedangkan box system sebanyak 41,6%Kata kunci: Kanker servik, box system, brakiterapi, respon terapi, survival